FAKTOR-FAKTOR YANG MEMPENGARUHI KETERANDALAN PELAPORAN KEUANGAN DAERAH KOTA KUPANG - Helda M Ala (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2020)
This study aims to analyze the influence offactors that affect the reliability of financial reporting in the city of Kupang,the influence of human resources on the reliability of regional financial reporting, the influence of information technology on the reliability of regional financial reporting, the effect of internal control on the reliability of regional financial reporting,and the effect of the quality of human resources on the use of information technology and the control of regional financial interventions on the reliability of regional financial reporting. This study shows that human resource capacity has a significant influence on the reliability of local government financial reporting, the use of information technology does not affect the reliability of Kupang City government financial statements, internal control has a significant influence on the reliability of Kupang financial reporting in the regional government. The results of this study explain the capacity of human resources, the use of information technology and the reliability of financial reporting together affect the reliability of regional financial reporting. From the results of the study it can be seen that the value of the statistical test F count value is 14.421> F table value is 2.87 with significant level 0,000 <0,05, then H4 is accepted. meaning if the independent variables together then the reliability of financial reporting in this study as the dependent variable will also increase.